The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3389/fnut.2022.984487
|View full text |Cite
|
Sign up to set email alerts
|

Predictive value of 25-hydroxyvitamin D level in patients with coronary artery disease: A meta-analysis

Abstract: BackgroundA consensus has not been made about the predictive value of blood vitamin D level in patients with coronary artery disease (CAD). This meta-analysis aimed to assess the association between blood 25-hydroxyvitamin D level and adverse outcomes in patients with CAD.MethodsTwo independent authors searched the articles indexed in PubMed and Embase databases until June 28, 2022. Cohort studies or post-hoc analysis randomized trials evaluating the value of 25-hydroxyvitamin D level in predicting cardiovascu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 31 publications
(53 reference statements)
1
2
0
1
Order By: Relevance
“…In this study, the RR was found to be 0.83 (95% CI from 0.37 to 1.86) in MACEs in patients with low Vit-D levels. All-cause mortality was also found to have an RR of 0.94 (95% CI from 0.39 to 2.26) [21]. The patient group in our study was similar to the stable coronary artery patient profile in a study in this meta-analysis.…”
supporting
confidence: 82%
“…In this study, the RR was found to be 0.83 (95% CI from 0.37 to 1.86) in MACEs in patients with low Vit-D levels. All-cause mortality was also found to have an RR of 0.94 (95% CI from 0.39 to 2.26) [21]. The patient group in our study was similar to the stable coronary artery patient profile in a study in this meta-analysis.…”
supporting
confidence: 82%
“…High VDD was demonstrated in patients with metabolic bone disorders [ 46 ], autoimmune diseases [ 47 , 48 , 49 ], including rheumatic disorders [ 50 , 51 , 52 , 53 ], inflammatory bowel diseases [ 54 , 55 ], infectious diseases [ 56 , 57 ], endocrine system disorders (type I diabetes mellitus, thyroid diseases, etc.) [ 58 , 59 , 60 ], cardiovascular [ 61 , 62 , 63 ], nervous system disorders [ 64 , 65 , 66 ], kidney diseases [ 67 ], chronic obstructive pulmonary disease [ 68 ], and tumors [ 69 ]. Also, for patients who take some drugs on a long-term basis, a negative impact on vitamin D metabolism was observed [ 70 , 71 ].…”
Section: Consensus Recommendationsmentioning
confidence: 99%
“…Проте накопичено достатньо даних щодо збільшення частки ДВД в осіб старших вікових груп [1,32,35], осіб з надмірною масою тіла та метаболічним синдромом [1,32,58], темною пігментацією шкіри [59]. Крім того, продемонстровано збільшення ДВД у хворих з метаболічними захворюваннями кісткової тканини [60], осіб з інфекційною [61,62] та автоімунною патологією [63,64,65], зокрема запальними захворюваннями кишечника [66,67], ревматичною патологією [68][69][70][71] тощо, захворюваннями ендокринної системи, зокрема цукровим діабетом [72,73], гіпогонадизмом [74], патологією щитоподібної залози [75,76] тощо, захворюваннями серцево-судинної [77][78][79][80], нервової системи [81][82][83], нирок [84], онкологічними захворюваннями [85], тривалим прийомом лікарських засобів з негативним впливом на метаболізм вітаміну D [86,87], а також зв'язок зі збільшеним рівнем смертності з різних причин [88][89][90][91]. Тому визначення сироваткового рівня 25(OH)D у цієї категорії осіб може бути корисним для ефективної профілактики й лікування ДВД [15,22,…”
Section: скринінг дефіциту вітаміну D у дорослихunclassified